3D printing objects as knowledge artifacts for a do-it-yourself approach in clinical practice: A questionnaire-based user study in the orthopaedics domain. (5th February 2018) - Cabitza, Federico; Locoro, Angela; Ravarini, Aurelio
Abstract : Purpose: The purpose of this paper is to investigate the phenomenon of the digital do-it-yourself (DiDIY) in the medical domain. In particular, the main contribution of the paper is the analysis and discussion of a questionnaire-based user study focused on 3D printing (3DP) technology, which was conducted among clinicians of one of the most important research hospital group in Lombardy, Italy. Design/methodology/approach: A general reflection on the notion of knowledge artifacts (KAs) and on the use of 3DP in medicine is followed by the research questions and by a more detailed analysis of the specialist literature on the usage of 3DP technology for diagnostic, training and surgical planning activities for clinicians and patients. The questionnaire-based user study design is then emerging from the conceptual framework for DiDIY in healthcare. To help focus on the main actors and assets composing the 3DP innovation roles in healthcare, the authors model: the DiDIY-er as the main initiator of the practice innovation; the available technology allowing the envisioning of new practices; the specific activities gaining benefits from the innovative techniques introduced; and the knowledge community continuously supporting and evolving knowledge practices. Findings: The authors discuss the results of the user study in the light of the four main components of our DiDIY framework and on the notion of KA. There are differences between high expertise, or senior, medical doctors (MDs) and relatively lower expertise MDs, or younger MDs, regarding the willing to acquire 3DP competences; those who have seen other colleagues using 3DP are significantly more in favor of 3DP adoption in medical practices, and those who wish to acquire 3DP competence and do-by-themselves are significantly more interested in the making of custom-made patient-specific tools, such as cutting guides and templates; there are many recurrent themes regarding how 3DP usage and application may improve medical practice. In each of the free-text questions, there were comments regarding the impact of 3DP on medical knowledge practices, such as surgical rehearsal, surgery, pathology comprehension, patient-physician communication and teaching. Originality/value: The 3DP adoption in healthcare is seen favorably and advocated by most of the respondents. In this domain, 3DP objects can be considered KAs legitimately. They can support knowledgeable practices, promote knowledge sharing and circulation in the healthcare community, as well as contribute to their improvement by the introduction of a new DiDIY mindset in the everyday work of MDs.